Parkinsonian central pain is linked to the connectivity of the nucleus accumbens and the anterior insula - Karel Joineau; Mathilde Boussac; Patrice Peran; David Devos; Jean Luc Houeto; Sophie Drapier; David Maltete; Jesus Aguilar; Estelle Harroch; Margherita Fabbri; Clémence Leung; Fabienne Ory-Magne; et al. (NeuroImage: Reports)
Pain is a frequent and disabling non-motor symptom of Parkinson’s Disease (PD). Yet, no treatment to date can efficiently reduce this pain. This article investigates the brain functional connectivity of PD patients with central pain and the effects of levodopa and oxycodone on this connectivity.Thirty-eight PD patients received either levodopa, oxycodone, or a placebo during an eight-week period. Pain intensity was evaluated using the Visual Analogue Scale and resting-state functional connectivity was measured before and after treatments. PD patients were also separated into two groups: responders and non-responders.At baseline, the intensity of pain was correlated with the connectivity between the anterior insula and the posterior cingulate cortex and between the nucleus accumbens, the brainstem, and the hippocampus. Levodopa and oxycodone had no specific effects on functional connectivity. Responders had a decrease in connectivity between the anterior insula and the posterior cingulate cortex, while non-responders showed an increase in connectivity.The correlation between pain intensity and specific brain connectivity may represent a “hyper-awareness” of pain and a distortion of learning and memory systems in PD patients with central pain, leading to a state of chronic pain. The placebo effect could explain the changes in connectivity that are associated with a potential reduction in pain awareness.